Atypical Presentations of Molar Pregnancy: Diagnostic Roles of Imaging, β‐Human Chorionic Gonadotropin Measurement, and p57 Immunostaining. (9th February 2016) - Mohamed, Sara A.; Al-Hendy, Ayman; Ghamande, Sharad; Chaffin, Joanna; Browne, Paul
Abstract : In modern practice, the diagnosis of molar pregnancy is made at an early gestational age. The opportunity to diagnose gestational trophoblastic disease (GTD) using sonography alone occurs less frequently. The classic appearance of a "snowstorm" in the endometrial cavity and bilateral theca lutein cysts still applies to the diagnosis of second‐trimester GTD. The diagnosis of first‐trimester GTD requires increased clinical suspicion. If the sonographic appearance of the pregnancy is atypical, GTD should be included in the differential diagnosis. Additional nonimaging criteria such as serial quantitative β‐human chorionic gonadotropin levels, pathologic examination, and p57 (cyclin‐dependent kinase inhibitor 1C protein) immunostaining can accurately confirm the diagnosis of GTD.